2008
DOI: 10.1097/chi.0b013e318172ef36
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Diffusion Tensor Imaging of the Fornix in Childhood- and Adolescent-Onset Schizophrenia

Abstract: These findings suggest that the early stages of schizophrenia are associated with a decrease in fornix volume without microstructural white matter changes. The volume differences may reflect an early insult to neighboring brain regions (i.e., hippocampus), that could decrease the number of efferent fibers without necessarily disrupting fiber integrity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 43 publications
1
29
0
Order By: Relevance
“…The fornix belongs to the Papez circuit known to be involved in cognitive and memory abilities for review44. MRI and in particular DTI methods in humans report similar connectivity defects in schizophrenic patients with disrupted fornix integrity4546474849 associated with alterations of resting state functional connectivity50 and defective memory organization5152. Other links between abnormal neuronal axonal tract formation and specific genes have been reported in both animal models and patients.…”
Section: Discussionmentioning
confidence: 96%
“…The fornix belongs to the Papez circuit known to be involved in cognitive and memory abilities for review44. MRI and in particular DTI methods in humans report similar connectivity defects in schizophrenic patients with disrupted fornix integrity4546474849 associated with alterations of resting state functional connectivity50 and defective memory organization5152. Other links between abnormal neuronal axonal tract formation and specific genes have been reported in both animal models and patients.…”
Section: Discussionmentioning
confidence: 96%
“…Tracking the fimbria-fornix complex is an important issue in studies dealing with neurological (e.g. epilepsy) or psychiatric disorders (such as schizophrenia) in which the structures connected by this pathway have been hypothesized to be crucially involved (48). We show also the possibility to visualize bundles running from the optic chiasm through optic tract and arriving at the lateral geniculate nucleus, forming the posterior part of the visual pathway.…”
Section: Fiber Tracking and Probability Mapsmentioning
confidence: 95%
“…In a structural MRI (sMRI) and fMRI study, Michael et al (2010) introduced three methods to identify correlations between sMRI and fMRI voxels within the whole brain, and observed that the linkage between gray matter and functional activation is stronger in healthy controls than in schizophrenia. In a combined sMRI and DTI study by Kendi et al (2008), it was noted that the early stages of schizophrenia are associated with a decrease in fornix volume without microstructural white matter changes and it was suggested that the volume differences may reflect an early insult to neighboring brain regions that could decrease the number of efferent fibers without necessarily disrupting fiber integrity. It is hoped that these multi-modality studies will lead to an understanding of significance of progressive brain changes over the course of illness.…”
Section: Diagnosis and Clinical Characteristicsmentioning
confidence: 99%